2022
DOI: 10.1038/s41598-022-22859-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ART outcome in patients with poor ovarian response according to POSEIDON criteria

Abstract: The aim of this study is to evaluate whether the patient-oriented strategies encompassing individualized oocyte number (POSEIDON) criteria can reflect the prognosis of controlled ovarian stimulation (COS) by comparing the results of assisted reproductive technologies (ART) between four POSEIDON and normal responder (NR) groups. In total, 225 patients were included in this retrospective observational study. The patients underwent various COS protocols and in vitro fertilization or intracytoplasmic sperm injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Lee et al compared ART outcome in patients with POR according to POSEIDON criteria and concluded that serum AMH level and patients' age had impacts on ART outcome, especially serum AMH level [31]. This nding is consistent with our study result, concluding that age is the most signi cant factor of predicting the outcome of ART treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Lee et al compared ART outcome in patients with POR according to POSEIDON criteria and concluded that serum AMH level and patients' age had impacts on ART outcome, especially serum AMH level [31]. This nding is consistent with our study result, concluding that age is the most signi cant factor of predicting the outcome of ART treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have indicated that women in POSEIDON groups 3 and 4 typically experience lower LBR compared to normoresponders or those in POSEIDON group 1 and 2 [ 6 ]. Recommended strategies for achieving one euploid blastocyst in these expected POR patients include high-dose gonadotropin administration (300–450 IU/day), oocyte/embryo pooling, and duostim/luteal phase oocyte retrieval protocols [ 4 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In practice, the POSEIDON classification delineates patients with POR into two categories: ‘unexpected POR’ (groups 1 and 2) and ‘expected POR’ (groups 3 and 4) [ 5 ]. Upon comparing these groups in terms of cumulative live birth rates, the highest rate of 22.6% was recorded in group 1, with this rate progressively declining to 4.8% in group 4 [ 6 ]. Given the notably low live birth rates (LBRs) in POSEIDON groups 3 and 4, numerous treatment modalities are recommended for these patients [ 4 ], albeit some lacking approval from the US Food and Drug Administration (FDA) for use with POR patients.…”
Section: Introductionmentioning
confidence: 99%
“…The assisted pregnancy strategies and clinical outcomes vary with different groups of POSEIDON patients. However, no definitive consensus has been reached r e g a r d i n g ho w t o f or m u l a t e in d i v i d u a l i z e d o va ri an hyperstimulation protocols for each POSEIDON group to attain maximal benefit (2)(3)(4). Some protocols do not require pituitary downregulation and these include the antagonist protocol, the non-downregulation protocol, and the progestin-primed ovarian stimulation protocol.…”
Section: Introductionmentioning
confidence: 99%